The Fibonacci Zeta-Function is Hypertranscendental - Steuding, J¨orn (CUBO, A Mathematical Journal, 2008)
Applying a theorem of Reich on Dirichlet series satisfying difference-differential equations, we show that the Fibonacci zeta-function satisfies no algebraic differential equation.